COVID‐19 and Supply Chain Disruption: Evidence from Food Markets in India(†) - Mahajan, Kanika (Wiley Periodicals, Inc., 2020)

(untitled) (Am J Agric Econ)
This paper looks at the disruption in food supply chains due to COVID‐19 induced economic shutdown in India. We use a novel dataset from one of the largest online grocery retailers to look at the impact on product stockouts and prices. We find that product availability falls by 10% for vegetables, fruits, and edible oils, but there is a minimal impact on their prices. On the farm‐gate side, it is matched by a 20% fall in quantity arrivals of vegetables and fruits. We then show that supply chain disruption is the main driver behind this fall. We compute the distance to production zones from our retail centers and find that the fall in product availability and quantity arrivals is larger for items that are cultivated or manufactured farther from the final point of sale. Our results show that long‐distance food supply chains have been hit the hardest during the current pandemic with welfare consequences for urban consumers and farmers.